Tracking in vivo dynamics of NK cells transferred in patients undergoing stem cell transplantation. Issue 9 (30th June 2014) - Killig, Monica; Friedrichs, Birte; Meisig, Johannes; Gentilini, Chiara; Blüthgen, Nils; Loddenkemper, Christoph; Labopin, Myriam; Basara, Nadezda; Pfrepper, Christian; Niederwieser, Dietger W.; Uharek, Lutz; Romagnani, Chiara
<x xml:space="preserve">Abstract</x> Haploidentical stem cell transplantation (haploSCT) offers an alternative treatment option for advanced leukemia patients lacking a HLA‐compatible donor. Transfer of NK cells represents a promising therapeutic option in combination with SCT, as NK cells can promote graft versus leukemia with low risk of GVH disease. In this study, we show results from a phase I/II trial in which 24 acute myeloid leukemia patients underwent haploSCT in combination with early transfer of unmodified NK cells and observed a promising 2‐year overall survival rate of 37%. By performing immunomonitoring and subsequent principal component analysis, we tracked donor NK‐cell dynamics in the patients and distinguished between NK cells reconstituting from CD34+ precursors, giving rise over time to a continuum of multiple differentiation stages, and adoptively transferred NK cells. Transferred NK cells displayed a mature phenotype and proliferated in vivo during the early days after haploSCT even in the absence of exogenous IL‐2 administration. Moreover, we identified the NK‐cell phenotype associated with in vivo expansion. Thus, our study indicates a promising path for adoptive transfer of unmodified NK cells in the treatment of high‐risk acute myeloid leukemia.